1994
DOI: 10.1007/bf00292249
|View full text |Cite
|
Sign up to set email alerts
|

Surface versus needle electrodes in determination of motor conduction time to the external anal sphincter

Abstract: Patients were referred to our neurophysiological department in order to investigate anorectal function. By the means of magnetic stimulation the total motor conduction can be determined. Only patients with normal latency of the pudendal nerve and normal EMG of the external anal sphincter were examined. Stimulation was carried out above the motor cortex with a MO between 80 and 100%. The recording was carried out in 22 patients with concentric needle electrodes and in the other 18 patients with surface electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 4 publications
1
13
1
4
Order By: Relevance
“…Our recorded latencies, amplitudes and the values of the intervals are lower than those described by Cauzinille (1997), probably as a consequence of using surface electrodes (Jost et al 1994;Musteață et al, 2013).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Our recorded latencies, amplitudes and the values of the intervals are lower than those described by Cauzinille (1997), probably as a consequence of using surface electrodes (Jost et al 1994;Musteață et al, 2013).…”
Section: Discussioncontrasting
confidence: 81%
“…In another study done on animals with CVS, BAERs recorded with needle electrodes showed that there is an increase in central wave latencies comparing with the control (healthy) group (Steiss et al, 1994). Till now there are only few studies performed in animals using surface electrodes (Jost et al, 1994;Musteață et al, 2013). In those studies the wave's morphology was preserved but the latencies were lower than those previously obtained with needle electrodes (Steiss et al, 1994, Cauzinille, 1997.…”
Section: Introductionmentioning
confidence: 95%
“…Our recorded latencies are lower than those described previously (Cauzinille 1997), possibly as a consequence of direct influence of using surface electrodes (Jost et al 1994). As expected, the wave's latency decreased inversely with the stimulus intensity.…”
Section: Discussionsupporting
confidence: 57%
“…Марка для оценки латентности М-ответа наруж-ного анального сфинктера при стимуляции полового нерва [9][10][11][12][13][14]. Регистрация вызванного моторного от-вета мышц тазового дна возможна при сегментарной магнитной стимуляции (МС) пояснично-крестцовой области с использованием игольчатых, стандартных внутрианальных или специальных ЭМГ-электродов [15][16][17][18][19].…”
Section: том 7 Volunclassified